A Facile Method to Fine‐Tune Polymer Aggregation Properties and Blend Morphology of Polymer Solar Cells Using Donor Polymers with Randomly Distributed Alkyl Chains. Issue 6 (10th October 2017) - Yao, Huatong; Li, Yunke; Hu, Huawei; Chow, Philip C. Y.; Chen, Shangshang; Zhao, Jingbo; Li, Zhengke; Carpenter, Joshua H.; Lai, Joshua Yuk Lin; Yang, Guofang; Liu, Yuhang; Lin, Haoran; et al.
Abstract: The device performance of polymer solar cells (PSCs) is strongly dependent on the blend morphology. One of the strategies for improving PSC performance is side‐chain engineering, which plays an important role in controlling the aggregation properties of the polymers and thus the domain crystallinity/purity of the donor–acceptor blends. In particular, for a family of high‐performance donor polymers with strong temperature‐dependent aggregation properties, the device performances are very sensitive to the size of alkyl chains, and the best device performance can only be achieved with an optimized odd‐numbered alkyl chain. However, the synthetic route of odd‐numbered alkyl chains is costly and complicated, which makes it difficult for large‐scale synthesis. Here, this study presents a facile method to optimize the aggregation properties and blend morphology by employing donor polymers with a mixture of two even‐numbered, randomly distributed alkyl chains. In a model polymer system, this study suggests that the structural and electronic properties of the random polymers comprising a mixture of 2‐octyldodecyl and 2‐decyltetradecyl alkyl chains can be systematically tuned by varying the mixing ratio, and a high power conversion efficiency (11.1%) can be achieved. This approach promotes the scalability of donor polymers and thus facilitates the commercialization of PSCs. Abstract : The structural and electronic properties of random polymers comprising a mixture of commercially available alkyl chains can be systematically tuned and a power conversion efficiency up to 11.1% can be achieved, which is one of the highest values to date for polymer:fullerene solar cells. These random polymers are easier to scale up compared to that obtained using odd‐numbered alkyl chains.